Extra- and intracellular distribution of cytokinins in the leaves of monocots and dicots - Jiskrová, Eva; Novák, Ondřej; Pospíšilová, Hana; Holubová, Katarína; Karády, Michal; Galuszka, Petr; Robert, Stéphanie; Frébort, Ivo (New biotechnology, 2016)
The plant hormones cytokinins are a convenient target of genetic manipulations that bring benefits in biotechnological applications. The present work demonstrates the importance of the subcellular compartmentalization of cytokinins on the model dicot plant Arabidopsis thaliana and monocot crop Hordeum vulgare. The method of protoplast and vacuole isolation combined with precise cytokinin analysis and recovery assay of a vacuolar marker protein were used to quantify the contents of individual cytokinin forms in the leaf extracellular space, cell interior and vacuole. The data obtained for wild type plants and in each case a specific mutant line allow comparing the effect of genetic manipulations on the hormone distribution and homeostatic balance of cytokinins in the modified plants.
Keywords: Mutation; Cell Compartmentation; Cytokinins; Plants, Genetically Modified; Hordeum; Protoplasts; mutace; Biotechnology; biotechnologie; extracelulární prostor; Plant Leaves; Extracellular Space; vakuoly; listy rostlin; regulátory růstu rostlin; Membrane Transport Proteins; intracelulární prostor; Vacuoles; cytokininy; proteiny huseníčku; geneticky modifikované rostliny; Arabidopsis Proteins; Plant Growth Regulators; kompartmentace buňky; membránové transportní proteiny; Intracellular Space; Arabidopsis; protoplasty; ječmen (rod)